2003
DOI: 10.1046/j.1600-0404.2003.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the quality of life in patients with epilepsy in Seoul, South Korea

Abstract: Psycho-social factors outweighed the physical factors in determining QOL in Korean epilepsy patients. Recognition of these factors will lead health professionals to develop different strategies to improve the QOL of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
94
3
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 22 publications
(35 reference statements)
14
94
3
8
Order By: Relevance
“…The differences were highly statistically significant on ANOVA (p value<0.001).This shows that education improves quality of life. Similar results were reported by Choi-Kwon S et al 11 Frequency of seizures per month was positively correlated with QOLIE-9 total scores (Pearson Correlation 0.622) and was highly statistically significant (p value <0.001), as also reported by Djibuti et al and Thomas et al 2,10 Duration of illness positively correlated with QOLIE-9 total scores (Pearson Correlation 0.118) and but was statistically insignificant (p value 0.242). Szaflarski et al found poor quality of life with increase duration of illness.…”
Section: Discussionsupporting
confidence: 88%
“…The differences were highly statistically significant on ANOVA (p value<0.001).This shows that education improves quality of life. Similar results were reported by Choi-Kwon S et al 11 Frequency of seizures per month was positively correlated with QOLIE-9 total scores (Pearson Correlation 0.622) and was highly statistically significant (p value <0.001), as also reported by Djibuti et al and Thomas et al 2,10 Duration of illness positively correlated with QOLIE-9 total scores (Pearson Correlation 0.118) and but was statistically insignificant (p value 0.242). Szaflarski et al found poor quality of life with increase duration of illness.…”
Section: Discussionsupporting
confidence: 88%
“…In one study, AnxD or major depressive episode (MDE) had a comparable negative impact on quality of life measured with the Quality of Life in Epilepsy Inventory-89 (QOLIE-89) while comorbid occurrence of both mood and anxiety disorders yielded a worse impact 12 . In another study of 154 outpatient adults with epilepsy, presence of anxiety symptoms was the most important factor in explaining a worse QoL 13 .…”
Section: Introductionmentioning
confidence: 94%
“…Многие авторы отмечают, что при применении в качестве доба-вочной терапии ПЭП последнего поколения, отмечается лучший профиль переносимости политерапии [77,78]. Следует отметить, что есть и другие данные: согласно ис-следованиям, проведенным в разных странах [79][80][81] у больных эпилепсией, получавших политерапию, отмеча-лись более низкие показатели качества жизни (КЖ), а при переводе с политерапии на монотерапию показатели КЖ улучшались [78,82,83].…”
Section: вероятность эффективности терапии при первой неудачеunclassified